Portuguese version of the EUROPEP questionnaire: contributions to the psychometric validation - Hugo Roque; Ana Veloso; Pedro L Ferreira
ABSTRACT OBJECTIVE To assess the construct validity and reliability of the Portuguese version of the European Task Force on Patient Evaluation of General Practice Care questionnaire. METHODS We applied the Portuguese version of the European Task Force on Patient Evaluation of General Practice Care to 392 users of 20 Family Health Units from the North of Portugal. The validity of the construct was evaluated by exploratory factor analysis, with the Principal Axis Factoring method, by orthogonal rotation (varimax procedure), by the Kaiser normalization criteria (eigenvalue ≥ 1). The factorability of the data matrix was verified by the Kaiser-Meyer-Olkin and Bartlett's sphericity test. We estimated the reliability by the indicator of internal consistency Cronbach's alpha. To analyze the correlations between satisfaction and loyalty, we used the Pearson correlations. The predictor effect of satisfaction on loyalty was analyzed by simple linear regression. RESULTS Satisfaction presented five robust and well individualized dimensions - medical care, nursing care, clinical secretariat services, accessibility, and organization of services - with alpha values between 0.86 and 0.97, good levels of internal consistency. The loyalty showed alpha value of 0.72, considered a reasonable internal consistency. The satisfaction was predictive of loyalty. CONCLUSIONS The Portuguese European Task Force on Patient Evaluation of General Practice Care questionnaire is a robust and reliable instrument to measure the satisfaction and loyalty of users of the Family Health Units.